Pengaruh Kualitas Jasa terhadap Kepuasan Nasabah di Baitul Mall Tamwil Provinsi Riau - Darmansyah; Amrizal; Nurwati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to analyze the effect of service quality on customer satisfaction at Baitul Mall Tamwil Berlian Gansal, Batang Gansal District, Indragiri Hulu Regency, Riau Province. This type of research uses a combination research method (mixed methods research). The sampling technique uses a non-probability sampling technique and the sampling method uses Slovin's theory and produces a research sample of 82 respondents who are customers of Baitul Mall Tamwil Berlian Gansal. Data collection techniques used are two methods, namely questionnaires or questionnaires and interviews. The hypothesis of this study is that there is an effect of service quality on customer satisfaction at Baitul Mall Tamwil Berlian Gangsal, Batang Gangsal District, Indragiri Hulu Regency, Riau Province. The results of research at Baitul Mall Tamwil Berlian Gansal which is located in the Batang Gangsal sub-district show that service quality has a significant effect on customer satisfaction and has a positive relationship, that there are differences in customer perceptions of service at BMT. Even though there are satisfied customers, there are still significant complaints and input from customers regarding service, communication, and facilities. BMT Berlian Gansal has been trying to take concrete steps to improve service quality according to customer feedback. With a focus on service standards, employee training, response to feedback, and a persuasive approach